Host genetic background impacts modulation of the TLR4 pathway by RON in tissue‐associated macrophages. Issue 7 (2nd July 2013) - Chaudhuri, Amitabha; Wilson, Nicholas S; Yang, Becky; Paler Martinez, Andres; Liu, Jinfeng; Zhu, Catherine; Bricker, Nicole; Couto, Suzana; Modrusan, Zora; French, Dorothy; Cupp, James; Ashkenazi, Avi
Abstract : Toll‐like receptors (TLRs) enable metazoans to mount effective innate immune responses to microbial and viral pathogens, as well as to endogenous host‐derived ligands. It is understood that genetic background of the host can influence TLR responsiveness, altering susceptibility to pathogen infection, autoimmunity and cancer. Macrophage stimulatory protein (MSP), which activates the receptor tyrosine kinase recepteur d'origine nantais (RON), promotes key macrophage functions such as motility and phagocytic activity. MSP also acts via RON to modulate signaling by TLR4, which recognizes a range of pathogen or endogenous host‐derived molecules. Here, we show that RON exerts divergent control over TLR4 activity in macrophages from different mouse genetic backgrounds. RON potently modulated the TLR4 response in macrophages from M2‐prone FVB mice, as compared with M1‐skewed C57Bl6 mice. Moreover, global expression analysis revealed that RON suppresses the TLR4‐dependent type‐I interferon gene signature only in FVB macrophages. This leads to attenuated production of the potent inflammatory mediator, tumor necrosis factor‐α. Eliminating RON kinase activity markedly decreased carcinogen‐mediated tumorigenesis in M2/Th2‐biased FVB mice. We propose that host genetic background influences RON function, thereby contributing to the variability in TLR4 responsiveness in rodents and, potentially, in humans. These findings provide novel insight into the complex interplay between genetic context and immune function.